1941
DOI: 10.1152/ajplegacy.1941.132.3.698
|View full text |Cite
|
Sign up to set email alerts
|

Is Histamine Able to Maintain an Augmented Pepsin Response Comparable to That of Pilocarpine?

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

1942
1942
1973
1973

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…This finding would support the suggestion that a washout of preformed pepsin does not totally explain the pepsin response following stimulation with these drugs (Bucher, Ivy, and Gray, 1941;Hirschowitz, London, and Pollard, 1957;Gillespie and Bowen, 1962;Makhlouf, McManus, and Card, 1967). The initial peak response could be compatible with such a washout effect, but the continuing steady state of pepsin secretion would suggest that both drugs are true stimulants of the pepsin-forming cells.…”
Section: Commentsupporting
confidence: 64%
“…This finding would support the suggestion that a washout of preformed pepsin does not totally explain the pepsin response following stimulation with these drugs (Bucher, Ivy, and Gray, 1941;Hirschowitz, London, and Pollard, 1957;Gillespie and Bowen, 1962;Makhlouf, McManus, and Card, 1967). The initial peak response could be compatible with such a washout effect, but the continuing steady state of pepsin secretion would suggest that both drugs are true stimulants of the pepsin-forming cells.…”
Section: Commentsupporting
confidence: 64%
“…Alternatively, it may be that the pepsin-secreting cells are also, to a slight degree, under histamine control (Bucher, Ivy, and Gray, 1941), so the reduction in pepsin secretion may also be due to a specific anti-histamine effect.…”
Section: Discussionmentioning
confidence: 99%
“…Babkin (1944) and others have argued that since the histamine-stimulated secretion of pepsin may be low and since repeated injections may cause a further fall in concentration, the histamine secretion represents only a washing out of pepsin from the gastric pits. Goodman (1938), however, found a rise in pepsin on repeated injection, while have criticized the deductions made from the "double histamine" method (see, e.g., Gilman and Cowgill, 1931), and Bucher, Ivy, and Gray (1941) suggest that histamine, like such substances as pilocarpine, should be regarded as a stimulant for pepsin. More recently, Bjorkman, Norden, and Uvnas (1943), using anaesthetized cats with the pylorus ligated, failed to find a rise in pepsin activity and indeed found a decline after histamine injection, whereas vagal stimulation caused a marked rise.…”
Section: Discusionsmentioning
confidence: 99%
“…Alley (1935) has even postulated an inhibitory effect ofhistamine on pepsin secretion. More recently, however, Bucher, Ivy, and Gray (1941) have claimed that pepsin is increased in the stomach of the dog after histamine injection ; this work has been strongly criticized by Babkin (1944). In man, a number of clinical studies (e.g., Polland, 1932) suggested a stimulation of pepsin output after histamine, and Toby (1937a) found that the peptic content of human gastric juice was as high as that produced by stimulation of the vagus inthedog.…”
mentioning
confidence: 99%